To Kill a Mockingbird - Lee, Harper (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
"Through the young eyes of Scout and Jem Finch, Harper Lee explores ... the irrationality of adult attitudes toward race and class in the Deep South of the 1930s. The conscience of a town steeped in prejudice, violence, and hypocrisy is pricked by the stamina and quiet heroism of one man's struggle for justice--but the weight of history will only tolerate so much"--Provided by publisher.
Keywords: Fathers and daughters -- Fiction; Race relations -- Fiction; Trials (Rape) -- Fiction; Southern States -- Fiction. -- Race relations